Reduction of Sphingosine Kinase 1 Phosphorylation and Activity in Plasmodium-Infected Erythrocytes - Sah, Raj Kumar; Pati, Soumya; Saini, Monika; Boopathi, Pon Arunachalam; Kochar, Sanjay Kumar; Kochar, Dhanpat Kumar; Das, Ashis; Singh, Shailja (Frontiers in Cell and Developmental Biology, 2020)
Sphingosine-1-phosphate (S1P), a bioactive lipid mediator is involved in an array of biological processes and linked to pathological manifestations. Erythrocyte is known as the major reservoir for S1P as they lack S1P degrading enzymes (S1P lyase and S1P phosphohydrolase) and harbor sphingosine kinase-1 (SphK-1) essential for sphingosine conversion to S1P. Reduced S1P concentration in serum was correlated with disease severity in patients with Plasmodium falciparum and Plasmodium vivax infections. Herein, we aimed to identify the underlying mechanism and contribution of host erythrocytes towards depleted S1P levels in Plasmodium infected patients vs. healthy individuals. The level and activity of SphK-1 were measured in vitro in both uninfected and cultured P. falciparum infected erythrocytes. Infected erythrocytes demonstrated a significant decrease in SphK-1 level in a time-dependent manner. We found that, 10 to 42 hours post invasion (hpi), number of rings, trophozoites and schizonts were predominantly reduced to ~50% as compared to uninfected erythrocytes. We next analyzed the phosphorylation status of SphK-1, a modification responsible for its activity and S1P production, in both uninfected control and Plasmodium infected erythrocytes. Almost ~50% decrease in phosphorylation of SphK-1 was observed that could be corroborated with significant reduction in the production and release of S1P in infected erythrocytes. Serum S1P levels were, studied in parallel in P. falciparum (N = 15), P. vivax (N = 36) infected patients and healthy controls (N = 6). The findings revealed that S1P concentration was significantly depleted in uncomplicated malaria cases and was found to be lowest in complicated malaria and thrombocytopenia in both P. falciparum and P. vivax infected groups (p < 0.01**). The lower serum S1P level could be correlated with the reduced platelet count defining the role of S1P level in platelet formation. In conclusion, erythrocyte SphK-1 and S1P levels were studied in Plasmodium infected individuals and erythrocytes that helped in characterizing the complications associated with malaria and thrombocytopenia, providing insights into the contribution of host-erythrocyte biology in malaria pathogenesis. Finally, this study proposes the use of S1P and its analogue as a novel adjunct therapy for malaria complications.